BCG Vaccine Cross-protection from COVID-19: Statistical Study through Data Science - et. al., Dr.S.S. Sridhar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
COVID-19, caused by SARS-COV-2 virus, has spread to almost all the countries in the world. Much like the SARS pandemic in 2002 and 2003, conventional control measures like travel restriction and patient isolation are being used to control spread of COVID-19. However, the morbidity rate of COVID-19 is still more than 1. Despite the high morbidity rate in all the countries COVID-19 has spread to, mortality rate due to COVID-19 varies greatly between different countries. Through a few recent epidemiological studies, it has been suggested that a negative association between national BCG vaccination policy and prevalence and mortality of COVID-19 exists. It has been observed that countries with BCG in their national immunisation programs have a lower mortality rate than countries without BCG in their national immunisation programs. We survey public datasets and repositories from websites like BCGAtlas, WHO, John Hopkins GitHub and World Bank, to understand and predict, with the power of data science, the implications of a plausible BCG cross-protection from severe COVID-19. We study COVID-19 related statistics to understand the spread of the disease, compare it with other countries to understand the role of cross-protective vaccines like BCG.